Anti-COVID-19 natural products are spotlights for drug discovery and development - Pawar, Rajendra Singh; Dimri, Mayank; Maithani, Alok (Asian Journal of Pharmaceutical Research and Development, 2020)
Traditional plants and marine natural products have plausible medicinal compounds of anti-COVID-19 potential. They became spotlights for the development and discovery of new marketable antivirals. The global COVID-19 pandemic invigorated medicinal chemists to evolve new feasible ideas for the non-toxic medications.